A Prototype Iot Temperature And Humidity Monitoring Esp32 Based Via Thing Speak - Pinasthika Putri; Mechelle Angela Saragi; Yudha Anggia El Hakim Hasibuan; Zihan Refani Sihombing; Solly Aryza (Sean Institute, 2025)
Internet of Thingsis one of the latest technologies in real-time data management, especially for temperature and humidity monitoring. This study develops a prototype of an ESP32-based IoT system that is integrated with the ThingSpeak platform for temperature and humidity monitoring. The system uses a DHT22 sensor for data collection, while the ESP32 acts as the main controller that sends data to ThingSpeak via a Wi-Fi connection, and displays data on an OLED Display. Tests were conducted in regular and air-conditioned rooms, showing significant differences in humidity. Air-conditioned rooms show humidity within normal limits (45-65%), while regular rooms reach 70%. The data sent to ThingSpeak is visualized in a graph with details of the data sending time, based on the results of this study it is proven that the designed system can display temperature and humidity data in real-time on ThingSpeak, and has the potential to be applied on a wider scale.